Pengaruh Loyalitas Karyawan dan Work Life Balance Terhadap Produktivitas Kerja pada PT. Hasjrat Abadi Divisi Yamaha 3S Ahmad Yani Gorontalo - Sis Hernanda Hasan; Lisda L. Asi; Robiyati Podungge (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to determine the Effect of Employee Loyalty and Work-Life Balance on Work Productivity at PT. Hasjrat Abadi Yamaha 3S Division Ahmad Yani Gorontalo. The sample in this study is 35 employees. The approach in this study uses quantitative data collection techniques using observation, interviews and questionnaires (questionnaires). The data analysis technique uses multiple linear regression with analysis tools using the Statistical Program for Social Science (SPSS) version 26. Based on the results of the regression analysis of Employee Loyalty (X1), a significance value of 0.000 < from 0.05 and a t-value of 5.052 > t table 2.032, it can be concluded that the Employee Loyalty variable has a significant effect on Work Productivity. For Work Life Balance (X2), the significance value is 0.003 < from 0.05 and the t-value is calculated 3.236 > t table 2.032, it can be concluded that the Work-Life Balance variable has a significant effect on Work Productivity. Based on the results of the F test (simultaneous) that F calculated 19,129 > F table 3,284 and the significance value was 0.000 < 0.05. The results of the study show that 1) Employee Loyalty has a significant positive effect on Work Productivity. 2) Work Life Balance has a significant positive effect on Work Productivity. 3) Employee Loyalty and Work-Life Balance simultaneously have a significant positive effect on Work Productivity. The determination coefficient in this study has an effect of 0.738 or 73.8%. The remaining 26.2% were influenced by variables that were not studied in this study, such as job training, compensation, morale, and teamwork.